2007
DOI: 10.1177/102425890701300409
|View full text |Cite
|
Sign up to set email alerts
|

The puzzles of union density in Norway

Abstract: E SummaryThe level of union density in Norway is medium high, in contrast to the other Nordic countries where high density levels are supported by unemployment insurance funds. Developments in union density over time are stable in Norway, contrary to developments in most western European countries outside the Nordic region. This article traces the effects of unemployment insurance funds by comparing density levels in Norway with those in Finland and Sweden. In addition, the stability witnessed in union density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Using micro-data files for 34 countries Blanchflower (2007) found that, prior to 2005, union density rates peaked in midlife maximizing in the mid to late 40s. 3 4 This U-shaped, or hump shaped, pattern was also found subsequently for Norway by Nergaard and Stokke (2007) and Posthuma (2009) in the World Values Survey, 1999. Blanchflower found it made little difference whether controls were included, such as education, gender, race, occupation, location and so on; the probability of being a union member peaked in midlife.…”
Section: Introductionmentioning
confidence: 62%
“…Using micro-data files for 34 countries Blanchflower (2007) found that, prior to 2005, union density rates peaked in midlife maximizing in the mid to late 40s. 3 4 This U-shaped, or hump shaped, pattern was also found subsequently for Norway by Nergaard and Stokke (2007) and Posthuma (2009) in the World Values Survey, 1999. Blanchflower found it made little difference whether controls were included, such as education, gender, race, occupation, location and so on; the probability of being a union member peaked in midlife.…”
Section: Introductionmentioning
confidence: 62%
“…However, this is not the only difference between Norway and the other countries. According to Nergaard and Stokke (2007), the sectoral distribution of trade union density is very similar in Norway, Denmark and Sweden: very high in the public sector, high in manufacturing and low in the private service sector. However, the gap between density levels in the different sectors is much higher in Norway than in other Nordic countries.…”
Section: Discussionmentioning
confidence: 99%
“…Schnabel (2013) has shown that the decline in union density between 1980 and 2010 was 27 percentage points lower in countries with a Ghent system; indeed densities actually climbed until the 1990s in the Nordic countries, as Figure 1 shows. All Nordic countries except Norway, which since 1938 has operated a compulsory system (Nergaard and Stokke, 2007), still maintain a Ghent system where insurance against unemployment is based on voluntary UIF membership. It is worth noting that union density in Norway has been steady at round 55 percent for the past 15 years, which is consistent with the argument that declining trade union density in the Nordic Ghent countries is related to institutional changes to unemployment insurance benefits and the institutional arrangements governing the UIFs.…”
Section: The Link Between Uifs Trade Unions and The New Trajectoriesmentioning
confidence: 99%